Impedance studies on Ca0.5Sr0.5Cu3Ti4O12 ceramic oxide - Mustafa, Mazni; Wan Yusoff, Wan Mohamad Daud; Talib, Zainal Abidin; Shaari, Abdul Halim; Primus, Walter Charles (Universiti Pertanian Malaysia Press, 2009)
Ca0.5Sr0.5Cu3Ti4O12 (CSCTO) ceramic oxide was prepared using solid state reaction technique. Impedance measurement was done using High Dielectric Resolution Analyzer (Novocontrol Novotherm) from 30°C to 250°C, in the frequency range of 10-2 to 106 Hz. X-ray diffraction pattern showed a single phase with a cubic structure. In the complex impedance plot, three semi-circles were observed; these represented the grain, grain boundary and electrode effect responses. The semi-circles were fitted using a series network of three parallel RC circuits. The resistance was found to increase with the decreasing temperature. The activation energies, E a, obtained from the Arrhenius plots of CSCTO, were 0.31 eV and 0.73 eV for grain and grain boundary conductivity, respectively. The value of the grain energy was revealed as smaller than the grain boundary energy, due to the semi-conducting grain and the insulating grain boundary characteristic (Sinclair et al., 2002).